Killing, Extortion, and Fraud in Nanjing City in 1593–1594. (2nd July 2020) - Dardess, John W.
Abstract : A chance find of a file of legal cases handled by the Nanjing Court of Judicial Review in 1593 and the Nanjing Ministry of Justice in 1594 casts some rare light on how life was lived in the homes and markets and, in two instances, privileged households in Nanjing city. This sort of street-level information is ordinarily very difficult to unearth.